Heating energy balance and biomass consumption for the residential sector in the Po Valley. (December 2022) - Marigo, Marco; Zulli, Fabio; Pillon, Silvia; Susanetti, Laura; De Carli, Michele
Highlights: The assessment of energy consumption biomass combustion in the residential sector of the Po Valley is presented. Both a bottom-up physical-based simulation model and a statistical approach were used. The application of the presented model to other case studies is derirable. The estimated final biomass consumption ranges between 89.5 TJ and 95.4 TJ. The thermal energy provided by biomass combustion is about 14% for pellets and about 86% for wood logs. Abstract: In Northern Italy, woody biomass is widely used as an energy carrier for domestic heating systems; this leads to lower CO2 emissions, but some concerns are due to particulate matter emissions. The present paper compares three methodological approaches to estimate biomass consumption for residential heating in the Italian Po Valley using data aggregation and dynamic simulations. The first deals with the recent sample survey carried out within the LIFE + PREPAIR project, which quantifies the number and age of biomass appliances and estimates their consumption. The second approach consists of indirect estimation of biomass consumption based on reference buildings' dynamic simulations combined with data mining derived by institutional bodies. The third approach is a direct energy calculation which estimates the consumption starting from the biomass appliances stock. The different approaches have shown a good consistency with an estimated annual biomass consumption in the Po Valley ranging between 89 PJ and 95 PJ, corresponding to 15 % of the total fuel consumption. Part of this energy (14 %) is produced by the combustion of pellets (about 1 Mt) and the remaining part corresponds to the combustion of wood logs (about 5.5 Mt). These results show that, based on available information, multiple approaches to estimate residential biomass consumption can be adopted; applying the model to different years and case studies is desirable. This estimation is necessary as an input to air emission evaluation and, therefore, to support policy makers in implementing and monitoring effective air quality measures to reduce air pollution in the Po Valley.